Patellar tendon: From tendinopathy to rupture - Federica Rosso; Davide Edoardo Bonasia; Umberto Cottino; Federico Dettoni; Matteo Bruzzone; Roberto Rossi (Elsevier, 2015)
Patellar tendinopathy is very common in patients complaining of anterior knee pain. Its aetiology is still unclear, but neovascularisation seems to play a role. Different treatments have been proposed overtime, from rehabilitation to platelet-rich-plasma injections, but there is no agreement on the best treatment protocol. The final stage of patellar tendinopathy is patellar tendon rupture. In these cases surgical treatment is often required. The aim of this literature review is to focus on the aetiology, diagnosis, and treatment of both patellar tendinopathy and rupture. We report the conservative treatments proposed for patellar tendinopathy and the surgical techniques described for its rupture.